Seed-Coat Pigmentation Plays a Crucial Role in Partner Selection and N2 Fixation in Legume-Root–Microbe Associations in African Soils - Sanjay K. Jaiswal; Felix D. Dakora (Plants, 2024)
Legume–rhizobia symbiosis is the most important plant–microbe interaction in sustainable agriculture due to its ability to provide much needed N in cropping systems. This interaction is mediated by the mutual recognition of signaling molecules from the two partners, namely legumes and rhizobia. In legumes, these molecules are in the form of flavonoids and anthocyanins, which are responsible for the pigmentation of plant organs, such as seeds, flowers, fruits, and even leaves. Seed-coat pigmentation in legumes is a dominant factor influencing gene expression relating to N2 fixation and may be responsible for the different N2-fixing abilities observed among legume genotypes under field conditions in African soils. Common bean, cowpea, Kersting’s groundnut, and Bambara groundnut landraces with black seed-coat color are reported to release higher concentrations of nod-gene-inducing flavonoids and anthocyanins compared with the Red and Cream landraces. Black seed-coat pigmentation is considered a biomarker for enhanced nodulation and N2 fixation in legumes. Cowpea, Bambara groundnut, and Kersting’s bean with differing seed-coat colors are known to attract different soil rhizobia based on PCR-RFLP analysis of bacterial DNA. Even when seeds of the same legume with diverse seed-coat colors were planted together in one hole, the nodulating bradyrhizobia clustered differently in the PCR-RFLP dendrogram. Kersting’s groundnut, Bambara groundnut, and cowpea with differing seed-coat colors were selectively nodulated by different bradyrhizobial species. The 16S rRNA amplicon sequencing also found significant selective influences of seed-coat pigmentation on microbial community structure in the rhizosphere of five Kersting’s groundnut landraces. Seed-coat color therefore plays a dominant role in the selection of the bacterial partner in the legume–rhizobia symbiosis.